Desmosomes in Developing Human Epidermis - Sirkku Peltonen; Laura Raiko; Juha Peltonen (Hindawi Limited, 2010)
Desmosomes play important roles in the cell differentiation and morphogenesis of tissues. Studies on animal models have greatly increased our knowledge on epidermal development while reports on human developing skin are rare due to the difficult accessibility to the samples. Although the morphology of periderm cells and the process how the epidermis develops very much resemble each other, the timetable and the final outcome of a mature human epidermis markedly differ from those of murine skin. Even the genetic basis of the junctional components may have profound differences between the species, which might affect the implementation of the data from animal models in human studies. The aim of this review is to focus on the development of human skin with special emphasis on desmosomes. Desmosomal development is mirrored in perspective with other simultaneous events, such as maturation of adherens, tight and gap junctions, and the basement membrane zone.